2005
DOI: 10.1161/01.res.0000152968.71868.c3
|View full text |Cite
|
Sign up to set email alerts
|

Akt Mediates the Cross-Talk Between β-Adrenergic and Insulin Receptors in Neonatal Cardiomyocytes

Abstract: Abstract-Upregulation of the sympathetic nervous system plays a key role in the pathogenesis of insulin resistance.Although the heart is a target organ of insulin, few studies have examined the mechanisms by which ␤-adrenergic stimulation affects insulin sensitivity in cardiac muscle. In this study, we explored the molecular mechanisms involved in the regulation of the cross-talk between ␤ adrenergic and insulin receptors in neonatal rat cardiomyocytes and in transgenic mice with cardiac overexpression of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 44 publications
7
108
0
6
Order By: Relevance
“…In contrast to our results in adipocytes, however, Epac appeared to be a positive, and PKA a negative, regulator of this process. On the other hand, in cardiomyocytes, short term stimulation with adrenaline increased insulininduced PKB phosphorylation via PKA [37], in agreement with our findings in adipocytes. Also the study on hepatocytes showed possible involvement of PKA in insulin+glucagon or leptin+glucagon-induced PKB activation [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to our results in adipocytes, however, Epac appeared to be a positive, and PKA a negative, regulator of this process. On the other hand, in cardiomyocytes, short term stimulation with adrenaline increased insulininduced PKB phosphorylation via PKA [37], in agreement with our findings in adipocytes. Also the study on hepatocytes showed possible involvement of PKA in insulin+glucagon or leptin+glucagon-induced PKB activation [20].…”
Section: Discussionsupporting
confidence: 92%
“…In other cell types various results have been obtained. In cardiomyocytes [37], isoproterenol-induced phosphorylation of PKB was PKA and PI3K dependent, whereas, in COS cells [19], cAMP-induced PKB activation was PKA-dependent but PI3K-independent, and in Sertoli cells [39], dbcAMP-induced activation of PKB was PKAindependent but PI3K-dependent. These data strengthen the hypothesis about the specificity of certain signalling events with regard to different tissues.…”
Section: Discussionmentioning
confidence: 94%
“…3d). In addition to inducing CREB phosphorylation, β-adrenergic agonism also activates Akt and extracellular signal-related kinase (ERK) [5,17,18]. In contrast to the two phases of ERK activation by glucagonlike peptide 1 in the pancreatic beta cells, ERK activation induced by isoprenaline treatment in TGP52 cells is monophasic [19].…”
Section: /β2armentioning
confidence: 99%
“…Given that prolonged β adrenergic receptor stimulation in cardiomyocytes inhibited insulin receptor signaling (22), we hypothesized that β adrenergic receptor blockade might improve insulin receptor signaling. As expected, in addition to reducing inhibitory IRS-1 phosphorylation, propranolol administration promoted tyrosine phosphorylation of IRS-1 and phosphorylation of Akt.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%